Characterization of fly ash-cement paste and molecular structure in the presence of seawater by 27Al and 29Si MAS NMR spectroscopy - Li, Jinhui; Liu, Xinquan; Yang, Qingrui; Hou, Dongshuai; Hu, Xiaoxia; Ye, Qiang; Wang, Di; Ding, Qingjun (Construction & building materials, 2020)
•Incorporating fly ash in cement paste resist the degradation for aluminate-silicate chains.•The activation effect of seawater on fly ash is more pronounced especially in the early curing age.•Delaying the initial exposure age of the paste can reduce the amount of AFt and alleviate its expansion. Cement-based materials commonly suffer attacking from detrimental ions in marine environment and the degradation mechanism for material is complicated. To study the effect of curing stage on degradation process, the microstructure and molecular structure of fly ash and Portland cement paste curing at 1 day, 7 day, 14 day and 28 day with w/c ratio of 0.35 in seawater solutions for 90 days are investigated by 27Al and 29Si magic-angle spinning (MAS) NMR spectroscopy, XRD and SEM tests. It reveals that more Friedal salt and Aft hydration phase are formed when the samples curing at early stage (1 day) are immersed in the sea water due to unhydrated and porous microstructure subject to sulfate and chloride ions. Based on the 29Si spectrum analysis, the increasing of mean silicate chain length of C-S-H and the degrading for AlO4/SiO4 ratio demonstrate that detrimental ions in seawater lead to the de-aluminization and polymerization for the cement hydrate. Furthermore, 27Al NMR test observes phase transformation from Al[4] in C-S-H gel to Al[6] Aft phase for samples in marine environment. Prolonging the curing age and incorporating fly ash in cement paste can significantly help resist the degradation for aluminate-silicate chains in C-S-H gel and aluminate phase transformation. More importantly, the hydration degrees for cement and fly ash computed separately illustrate that the aggressive ions in seawater act as activating role on fly ash, contributing to the secondary hydration of fly ash–cement paste. The activation effect is more pronounced for samples suffer to marine environment especially in the very early curing age, which significantly help resist aggressive ions as the cement paste in low hydration degree. Hopefully, this study can provide valuable insights on design of durable and sustainable marine concrete.